An approach to making students autonomous readers of the english language (2001)
The purpose of this paper is to point out the need to make students autonomous readers through the development of thinking skills such as the ability to classify, compare, deduce, induce and synthesise and reading strategies (prediction, global understanding of a text, inferences, and deduction of meaning through vocabulary).